Glucocorticoid receptor isoforms and effects of glucocorticoids in ovulated mouse oocytes and preimplantation embryos†. Issue 2 (5th September 2018) - Čikoš, Štefan; Babeľová, Janka; Špirková, Alexandra; Burkuš, Ján; Kovaříková, Veronika; Šefčíková, Zuzana; Fabian, Dušan; Koppel, Juraj
Abstract: To investigate possible involvement of glucocorticoid receptor (GR) in mediating effects of maternal stress or therapeutically administered glucocorticoids on early embryo, we analyzed the expression of GR subtypes in ovulated mouse oocytes and preimplantation embryos. RT-PCR analysis results showed that GRα and GRγ transcripts are relatively highly expressed in mouse oocytes, and both transcripts are present at lower amounts in preimplantation embryos. We also detected low expression of two other splice variants, GRβ and a transcript orthologous to the human GR-P subtype, mainly at the blastocyst stage. Using western blot analysis, we detected several GR protein bands that differed in size between oocytes and preimplantation embryos. To compare the effects of corticosterone (a major endogenous glucocorticoid in rodents) and dexamethasone (a synthetic glucocorticoid) on early embryos, we cultured mouse preimplantation embryos in the presence of these glucocorticoids. Corticosterone showed a strong inhibitory effect on embryo development (starting from a 50 μM concentration), without a significant influence on apoptosis incidence. On the other hand, dexamethasone induced apoptosis in early embryo cells (starting from a 1.5 μM concentration), and its effect on embryo development was less detrimental than that found with the same dose of corticosterone. In summary, our results showed that different GR subtypes are expressed in ovulated mouse oocytes and preimplantation embryos and that the composition of GR subtypes changes during early embryo development. Moreover, we found significant differences in the effects of the two glucocorticoids on early embryo development, which might be associated with activation of different GR subtypes. Abstract : Different glucocorticoid receptor subtypes are expressed in ovulated mouse oocytes and preimplantation embryos, and two glucocorticoid molecule types differ in their effects on preimplantation embryo development.